The development of political settlements in Uganda from independence to the present day: Background study for the CASH-IN research programme - Malin J. Nystrand; Bruno L. Yawe (Roskilde University, Department of Social Sciences and Business, Socio-Economic Research Centre (SECO), 2024)
This paper analyses political developments in Uganda from independence in 1962 until 2021. It applies a version of the political settlement approach in which power relations in society are analysed along the following five dimensions: vertical relations, horizontal relations, regime financing, ideology, and relations with external actors. The purpose of this analysis is to provide a foundation for a subsequent analysis of the politicization of social cash-transfer programmes in Uganda. The systematic historical analysis of five aspects of the political settlement that has existed throughout Uganda's whole post-independence history also adds value to previous political settlement analyses of Uganda by providing a rich understanding of the deep roots of some aspects of its political settlements, thus illuminating both continuities and changes over time. It also illustrates how political settlements change slowly and gradually, thereby highlighting the need for deep contextual knowledge in understanding the underpinnings of political development and politicization. The long-term continuities in Uganda's political development, which has spanned several regimes since independence, with its roots in the colonial and pre-colonial periods, include a weak democratic tradition, a strong role for the military, a lack of social cohesion perpetuated by patronage, and the strong influence of external actors. Changes that can be discerned from a longterm perspective include shifting economic policies from a state-led to a neoliberal paradigm; differences in political ideologies, where the 'broad-based government' vision of the early NRM regime was perhaps the most visionary; shifting alliances between the ruling elite and various domestic social groups; and the more recent attempts to gradually reduce dependence on Western countries and institutions. This paper draws out the implications of this analysis for the politicization of social cash transfers. First, there is no sign that social cash transfers or social protection in general are being used as a political tool for creating strong state-society relations in Uganda, as this would not be in line with the dominant neoliberal and conservative ideologies. What is more likely, based on the strong role of patronage in securing regime support, is that certain groups might be targeted based on a perceived need to boost political support in that particular group at a particular point in time. In this regard, the strong grassroots networks that the NRM has built throughout the country, extending into rural areas, where local government institutions are used to galvanize support for the party, could be used for the politicization of cash transfers. Whether that is the case is an empirical question. Another feature worth exploring is the involvement of the military in civilian government activities, including the provision of services, and the question of how this affects state-society relations. The Ugandan government cannot at present implement large-scale social protection programmes without international funding, primarily from Western countries and institutions. Given the increasing tensions in relations between the Ugandan government and Western donors, it is unlikely that the Ugandan regime would expand activities that exacerbate international dependence, thus further diminishing the likelihood of an extensive expansion of social cash transfers. When analysing the politicization of social cash transfers by non-state actors, which by and large are funded by Western international donors, all the above aspects have to be considered. What relations does such provision create between providers and recipients? How are these relations affected by, and how do they affect, the role of social cash transfers and social protection in the Ugandan political settlement? If government programmes and resources are to a large extent used as patronage, i.e. to target certain groups to boost or gain support, the main question for understanding the politicization of non-state provision becomes how non-state resources complement or compete with these logics.
Keywords: 330; Politik; Öffentliche Sozialleistungen; Soziale Sicherheit; Ideologie; Nichtregierungsorganisation; Uganda